Penerapan Model Sport Education untuk Meningkatkan Partisipasi Siswa pada Pembelajaran PJOK - Supriyana Jaka Susanta; Nursofiah Nasution; Khilyatul Masnunah; Singgih Wicaksono; Husin Husin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Student participation is an important aspect in creating an active, meaningful, and fun learning process. Students' physical, emotional, and cognitive involvement is influenced by internal and external factors in the educational environment. One of the models that can foster participatory skills is the Sport Education learning model. This study aims to describe the implementation steps, advantages, and disadvantages of the Sport Education model in learning PJOK at Madrasah Tsanawiyah Negeri 4 Klaten, Madrasah Aliyah Negeri 2 Rembang, and Madrasah Aliyah Negeri 1 Kebumen. This study used a qualitative approach with the research subject of PJOK teachers. Data were collected through interviews, observations, and documentation. The results showed that the implementation of Sport Education was carried out through five stages, namely season preparation, training sessions, competition implementation, peak competition, and reflection. The advantages of this model include being able to provide authentic learning experiences, increase motivation, build character, and train students' social skills. However, there are some disadvantages, such as competition pressure, limitations for students with low abilities, and relatively long preparation and time. In conclusion, the Sport Education model is feasible to be applied in learning PJOK as a strategy to increase student participation in madrasah.